Deksripsi kesesuaian usia kronologis dan usia dentalis melalui estimasi pertumbuhan ujung akar gigi premolar - Inne Suherna Sasmita; Lusi Epsilawati; Fadhlil Ulum Abdul Rahman (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: The purpose of this study was to find out the description of chronological age and dental age suitability through estimation of root growth of maxillary and mandibular premolar teeth. Material and Methods: This study was a descriptive study with cross-sectional approach performed on the maxillary and mandibular first and second premolars. Data was taken from 50 panoramic radiographs contained in the 2015-2016 RSGM Unpad archives. Analyzes were performed based on age predictions from the Demirjian table compared to chronological ages in several age groups. The data is then presented in tabular form. Results: This study shows that there is a high degree of concordance between chronological age and dental age through premolars 1 and 2, both upper and lower jaws of the Demirjian table in the initial phase of tooth root formation at 8 years chronological age and at the final phase of root apex closure at 12-13 years chronological age through the assessment of panoramic radiograph. Conclusion: Chronological age and dental age depend on the precise assessment of root growth of premolar 1 and 2 teeth in the maxillary and mandibular regions having a high degree of suitability in the early and final phases of tooth root formation which are seen more radiographically.